Rimeter structures in the magical practices of Ukrainian healers - Temchenko, Andriy (Ukrainian Peasant, 2024)
The goal is to gain new knowledge of the mythology of the spatial horizon during the formation of perimental constructions of the healing rite. The semantics of perimeter structures, which are used to model the ritual space, are examined in the paper. Scientific novelty. Isolating the perimeter as a separate spatial constant allows to slightly change the focus of the study of the spatial loci of the healing ritual. Conclusions. Healing-and-ritual texts in a certain way duplicate etiological myths, since they are supposed to reproduce the patient’s bodily integrity. For this purpose, spatial perimeter structures are modeled, within which stereotypes of the behavior of ritual performers are established and the functionality of household objects is changed. The limit value of the ritual space is adjusted depending on the purpose of its implementation. Thresholds, windows, chimneys, and doors are the critical points that “control” unauthorized exit outside the space established by the ritual. The symbolism of the corner is also associated with the quadrangle, the perpendicular breaks of which form “weak” places, which explains the reproduction of graphemes, monograms or bas-relief images on its outer contours. A symbolic form of organization of ritual space is the quadrangle, which demonstrates the way of cultural mastering of the horizontal. The binary opposite to the quadrilateral is the circle, which repeats natural forms. Hence there is the symbolism of the circle in funeral rites, which is seen as a way of returning to the natural state.